Resource use efficiency in cotton production in Palwal district of Haryana - KUMAR, SANT; KUMAR, NALINI RANJAN; JAIN, RAJNI; J, BALAJI S; JHAJHRIA, ABIMANYU; BANGARAJU, S V; AWAIS, MOHAMAD (The Indian Journal of Agricultural Sciences, 2021)
This paper examines productivity, profitability and resource use efficiency of cotton production in Palwal district of Haryana (India). The study is based on primary data collected from a total of 120 farmers selected randomly using two-stage sampling and data related to agricultural year 2017-18. Analytical tools like farm business analysis and production function approach is applied to summarise data. Results have revealed that large farms were more productive and earned higher profit from cotton production than small and medium farms. The regression results have shown that factors like human labour, phosphatic fertilizer, farm machinery and zinc had positive and significant impacts on cotton yield. The MVP of human labour, and phosphatic fertilizer were greater than unity indicating underutilization. However, other resources were applied in excess and suggested to utilize optimally to improve the yield of cotton.